(3cJGH GdYQhVs - (3CHh GdMSf SYjO Hf eSYOI GdeLGTYj HGdhdGA GdHdNj, GdCNaT GdGhSW,J (B215 (3g` s
(3ChdgG (B:s
(3gPG cJGH eG jYQa Hg hRf GdTYQ hGSJbGeJg ef GfcSGQg s
(3BNQgG (B:s
(3dCfg Ef LGR aj GdYQhV agh aj GdVQH CLhR hGddg CYde Je s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B101s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1438s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdYQhV hGdbhGais